Measurements of non-wetting phase trapping applied to carbon dioxide storage - Al-Mansoori, S.; Iglauer, Stefan; Itsekiri, E.; Pentland, C.; Bijeljic, B.; Blunt, M. (Elsevier, 2010)
We measure the trapped non-wetting phase saturation as a function of the initial saturation in sand packs. The application of the work is for CO2 storage in aquifers where capillary trapping is a rapid and effective mechanism to render injected CO2 immobile. The CO2 is injected into the formation followed by chase brine injection, or natural groundwater flow, which displaces and traps CO2 on the pore scale as a residual immobile phase. Current models to predict the amount of trapping are based on experiments in consolidated media, while CO2 may be stored in relatively shallow, poorly consolidated systems. We use analogue fluids at ambient conditions. The trapped saturation initially rises linearly with initial saturation to a value of approximately 0.13 for oil/water systems and 0.14 for gas/water systems. There then follows a region where the residual saturation is constant with further increases in initial saturation. This behaviour is not predicted by the traditional literature trapping models, but is physically consistent with unconsolidated media where most of the larger pores can easily be invaded at relatively low saturation and there is, overall, relatively little trapping. A good match to our experimental data was achieved with the trapping model proposed by Aissaoui.